Impact of anthropogenic sounds (pile driving, drilling and vessels) on the development of model species involved in marine biofouling - Cervello, Gauthier; Olivier, Frédéric; Chauvaud, Laurent; Winkler, Gesche; Mathias, Delphine; Juanes, Francis; Tremblay, Réjean (Frontiers in Marine Science, 2023)
The uncontrolled colonization of benthic organisms on submerged surfaces, also called biofouling, causes severe damage in the shipping and aquaculture industries. Biofouling starts with a benthic biofilm composed of a complex assemblage of microbes, bacteria and benthic diatoms, called microfouling, on which macrofouling invertebrate species settle and grow. Invertebrate larvae may use natural soundscapes to orientate inshore and choose their optimal habitat. Recent studies have demonstrated that ship sounds enhance the larval settlement and growth of several invertebrate species, such as mussels, associated with biofouling. Among invertebrates, effects of sound generated by offshore human activities are still poorly studied. This study aims to assess the effect of pile driving, drilling and vessel sounds on model species associated with micro and macrofouling. First, the biofilm development of Navicula pelliculosa and Amphora coffeaeformis was assessed, then, the larval development of the blue mussel (Mytilus edulis) was evaluated from the D-veliger to the postlarval stage. Mussel larvae and microalgae were exposed 12 h each day in tanks (Larvosonic) adapted to sound experiments under controlled conditions. All anthropogenic sounds induced a thinner N. pelliculosa biofilm coupled with a lower microalgae concentration. The drilling sound had a stronger effect on the biofilm thickness. The drilling sound significantly reduced the pediveliger settlement and the postlarvae clearance rate by 70.4% and tended to diminish settler sizes compared to control sound. Contrary to our expectation, pile driving tended to enhance larval recruitment by 22% (P=0.077) and the boat sound did not stimulate larval settlements or recruitment. Drilling sound generated a stressful acoustic environment for pediveliger settlements and postlarvae seem to maintain their shell valves closed to preserve energy. We identify potential causes and mechanisms involved in these impacts of anthropophony on larval ecology and microfouling dynamics.